Stepdaughters of History : Southern Women and the American Civil War - Clinton, Catherine, 1952- (Book collections on Project MUSE., 2016)
"In Stepdaughters of History, noted scholar Catherine Clinton reflects on the roles of women as historical actors within the field of Civil War studies and examines the ways in which historians have redefined female wartime participation. Clinton contends that despite the recent attention, white and black women's contributions remain shrouded in myth and sidelined in traditional historical narratives. Her work tackles some of these well-worn assumptions, dismantling prevailing attitudes that consign women to the footnotes of Civil War texts. Clinton highlights some of the debates, led by emerging and established Civil War scholars, which seek to demolish demeaning and limiting stereotypes of southern women as simpering belles, stoic Mammies, Rebel spitfires, or sultry spies. Such caricatures mask the more concrete and compelling struggles within the Confederacy, and in Clinton's telling, a far more balanced and vivid understanding of women's roles within the wartime South emerges. New historical evidence has given rise to fresh insights, including important revisionist literature on women's overt and covert participation in activities designed to challenge the rebellion and on white women's roles in reshaping the war's legacy in postwar narratives. Increasingly, Civil War scholarship integrates those women who defied gender conventions to assume men's roles - including those few who gained notoriety as spies, scouts, or soldiers during the war. As Clinton's work demonstrates, the larger questions of women's wartime contributions remain important correctives to our understanding of the war's impact. Through a fuller appreciation of the dynamics of sex and race, Stepdaughters of History promises a broader conversation in the twenty-first century, inviting readers to continue to confront the conundrums of the American Civil War."--Jacket.